PELAKSANAAN PROGRAM PENDIDIKAN KESETARAAN DI PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) KECAMATAN TERENTANG - Suhendro, Suhendro; Sulistyarini, Sulistyarini; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study would to determined the implementation of the equality package A, B and C education program in PKBM Merdeka Terentang District, Kubu Raya Regency. The research used descriptive method in the form of qualitative research. The data source in this study is the management of PKBM Merdeka, Terentang District, Kubu Raya Regency. Data collection techniques in this study were through interviews, observation, and documentation, while the data collection tools used were interview guides, observation and documentation. An analysis in this study presented in a qualitative descriptive manner using informants as many as four people, consisting of PKBM Merdeka administrators. The results of this study indicate that the implementation of the equality package A, B and C education program in PKBM Merdeka runs well according to what has been planned by the management, although there are some obstacles, the first is the lack of facilities and infrastructure such as computers, so that students are not obedient in the learning process too late was not even present, and during the learning process many students talked to themselves. Keywords: Equality Education, Implementation, Program